OUTCOME OF OPEN TENCKHOFF CATHETER INSERTIONS: 5 YEARS EXPERIENCE IN A MAJOR TERTIARY CENTRE IN CENTRAL SAUDI ARABIA - Hussain, Muhammad Ibrar; Al-Salamah, Saleh Mohammed; Aziz, Rizwan; Al-Qahatani, Hamad Hadi; Al-Ohay, Nasir Yazeed; Al-Jabar, Fahad (Journal of Ayub Medical College Abbottabad, 2013)
Background: Continuous ambulatory peritoneal dialysis (CAPD) has become a popular and established form of renal replacement therapy in patients with end-stage renal disease (ESRD). The objective of this study was to analyse the outcome of open Tenckhoff catheter insertions in patients with ESRD in term of catheter related complications. Methods: From December 2006 to November 2011, 337 Tenckhoff catheters were placed in 305 patients with ESRD for CAPD, by general surgeons in King Saud Medical City, Riyadh, Saudi Arabia. Medical record of all these patients was reviewed retrospectively regarding the demography, causes of ESRD, catheter related complications, and their management. Results: Mean age of the patients was 51.2±14.5 (range, 16-87years). Majority of the patients were female 164 (53.7%). Forty three patients (14.1%) had previous abdominal surgery. Diabetic nephropathy was the commonest (51.4%) primary cause of ESRD. Ninety three insertions (27.5%) were associated with complications. Post insertion peritonitis was the commonest complication (9.2%) in our series, followed by mechanical dysfunction (8.6%). Fifty two catheters (15.4%) were removed because of different complications. Follow up ranged between 4-47 months with a mean of 21.4±11.2 months. Conclusions: Open surgical approach is simple, safe, and effective method of Tenckhoff catheter insertion with an acceptable complication rate, provided patients are adequately optimized and prepared for surgery. Keywords: Continuous ambulatory peritoneal dialysis (CAPD), End stage renal disease (ESRD), Tenckhoff catheter, complications, peritonitis, mechanical dysfunction